Agglomeration and Firm Performance (Advances in Spatial Science, The Regional Science Series,, 2018)
This contributed volume studies and explains the effect that agglomeration exerts on a firm's innovation and performance. It presents new cases as well as new topics within the agglomeration phenomenon, exploring also their role under the Great Recession. Beyond the analysis of regions or clusters, this volume focuses on firms within agglomerations and captures this phenomenon from different perspectives, contexts and diverse literatures. Specifically, it looks at the question under what circumstances exert generate benefits on firms' performance, and how those gains are generated and distributed, usually asymmetrically, across agglomerated firms. In this context, the book addresses topics such as networks, collocation, labor mobility, firm's strategies, innovation, competitiveness and collective actions across a diverse set of literatures, including economic geography, business economics, management, social networks, industrial districts, international business, sociology or industry dynamics. .